A PRELIMINARY STUDY OF THE PALEOLITHIC AND NEOLITHIC CONTRIBUTION THE EUROPEAN MTDNA FLOW IN SHAPING THE GENETIC STRUCTURE OF RECENT BOSNIAN POPULATION - Ahmic, Adisa; Pojskic, Naris; Silajdzic, Elma; Hadziselimovic, Rifat (European Scientific Journal, ESJ, 2013)
The mitochondrial DNA (mtDNA) polymorphisms in Bosnian human population was analyzed by means of hypervariable segment I and II (HVSI and HVSII) sequencing and restriction fragment-length polymorphism analysis of the mtDNA coding region. The results suggest that shaping the genetic structure of recent Bosnian population likely to be affected by the expansion from the European glacial refuges area at the end of the Last Glacial Maximum (LGM), postglacial expansions from southwestern refuges of Europe, the Italian Peninsula and the dispersion in periods of more recent historical events, from the East European Plain. Especially interesting feature of the Neolithic expansion in this area is the ancient African/South Asian haplogroup N1a with the HVSI variant 16147G, which is almost absent in Europe. The haplotyps HVSI with variant 16147G suggest the colonization of the Northeast Bosnia region by Neolithic communities in the Early Neolithic period of expansion through Europe, as evidenced by the archaeological remains of the Starcevo culture.